Video Documentary of Situs Inversus Totalis in a Male Cadaver Module 5: Lungs and Heart - Gregory Casey; Lisa Campeau (Association of American Medical Colleges, 2014)
Abstract Situs inversus totalis is a condition in which the internal organs of the human body are transposed to opposite sides. On average, 1 in 20,000 individuals has situs inversus totalis. Situs inversus totalis requires students, educators, and clinicians to think differently about anatomy because the organs have been transposed to opposite sides. Although there have been many case reports published about this condition, there are no video documentaries illustrating the unique placement of the organs and their corresponding vasculature. This resource is part of a series of eight documentaries that provide video illustrations and quizzes on the detailed dissection of the situs inversus cadaver. In the two videos provided, the detailed dissection of the lungs and heart reveals the specific characteristics of the condition. For self or group study, individuals should watch the detailed dissection of the lungs and heart in situs inversus totalis and note the specific heart chamber details and vasculature placement as compared to normal anatomy. For instructional purposes, we advise distributing the quizzes associated with the video after the presentation to test for knowledge or for practice purposes. This publication could be especially useful to clinicians such as heart and lung surgeons preparing for an invasive procedures of these organs in patients with situs inversus totalis.